Research Progress of Failure Mechanism of Thermal Barrier Coatings at High Temperature via Finite Element Method - Zhong-Chao Hu (Coatings, 2020)
In the past decades, the durability of thermal barrier coatings (TBCs) has been extensively studied. The majority of researches emphasized the problem of oxidation, corrosion, and erosion induced by foreign object damage (FOD). TBCs with low thermal conductivity are usually coated on the hot-section components of the aircraft engine. The main composition of the TBCs is top-coat, which is usually regarded as a wear-resistant and heat-insulating layer, and it will significantly improve the working temperature of the hot-section components of the aircraft engine. The application of TBCs are serviced under a complex and rigid environment. The external parts of the TBCs are subjected to high-temperature and high-pressure loading, and the inner parts of the TBCs have a large thermal stress due to the different physical properties between the adjacent layers of the TBCs. To improve the heat efficiency of the hot-section components of aircraft engines, the working temperature of the TBCs should be improved further, which will result in the failure mechanism becoming more and more complicated for TBCs; thus, the current study is focusing on reviewing the failure mechanism of the TBCs when they are serviced under the actual high temperature conditions. Finite element simulation is an important method to study the failure mechanism of the TBCs, especially under some extremely rigid environments, which the experimental method cannot realize. In this paper, the research progress of the failure mechanism of TBCs at high temperature via finite element modeling is systematically reviewed.